Some Issues of Application of Article 309 of the Russian Federation Criminal Code - Anatolyi Vladimirovich Kuznetsov (Сибирское юридическое обозрение, 2011)
The author considers ways to optimize application of article 309 of Russian Federation Criminal Code.